Tagebuch. Il diario dell ritorno dal lager Liane Millu as an example of a description of the reality of the camp - Szwarc-Zając, Anna (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The text describes traumatic experiences of Italian writer Liana Millu`s reconstructed from some materials as manuscript of her diary written after an imprisonment in the Auschwitz-Birkenau camp.The diary is originally a small notebook (12 x 18 cm) and contains recollections rich in traumatical emotions connected to her fortunes and experiences.as an imprisoner. The author believes it`s a good material for psychoterapist as well as example of exiting from camp reality.